1984
DOI: 10.1111/j.1398-9995.1984.tb01981.x
|View full text |Cite
|
Sign up to set email alerts
|

Tree Pollen Allergy

Abstract: In a multi-centre study, comprising 16 clinics, 871 adult hay fever patients were studied. Most patients included had springtime hay fever. Skin prick tests were performed with 20 different tree or bush pollen (lignoses) allergens. RAST determinations were done with eight different tree pollen allergens in 590 patients. Birch pollen (BP) allergen gave the highest frequency of positive test results. The test results with the various tree pollen allergens in patients with BP allergy were compared with those in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…A majority of the subjects had higher specific IgE levels to rBetv 1 than to nQue a 1. It seems likely that these subjects have been exposed predominately to birch pollen and that the Que a 1 sensitization is the result of cross-reactive IgE antibodies originally developed against Bet v 1 [13, 14, 31]. Our cross-inhibition study using nQue a 1 and nBet v 1 supports the Bet v 1 cross-reactivity theory of acquiring Que a 1 sensitization in the 6 US and Swedish subjects studied.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A majority of the subjects had higher specific IgE levels to rBetv 1 than to nQue a 1. It seems likely that these subjects have been exposed predominately to birch pollen and that the Que a 1 sensitization is the result of cross-reactive IgE antibodies originally developed against Bet v 1 [13, 14, 31]. Our cross-inhibition study using nQue a 1 and nBet v 1 supports the Bet v 1 cross-reactivity theory of acquiring Que a 1 sensitization in the 6 US and Swedish subjects studied.…”
Section: Discussionsupporting
confidence: 70%
“…In Madrid, Spain, 14% of the pollen-allergic patients are sensitized to oak pollen [12], and in Sweden this number is 70–80% of the springtime pollen-allergic patients [13]. Que a 1 is an important oak pollen allergen and belongs to the PR-10 protein family.…”
Section: Introductionmentioning
confidence: 99%
“…Pollens appear seasonally and are reflected in the symptoms of patients with SR living in temperate climates. Recent studies have shown that grass pollen in Turkey [4,5,6,7,8], birch and grass pollens in northern Europe [17,18,19,20,21], ragweed pollen in America [22], and mugwort and olive pollens in the Mediterranean area [23,24,25,26,27] are the most common and important allergens of these regions. Since Turkey is located between Europe and Asia like a bridge, all four seasons can be present in different regions of the country at the same time of the year.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the rate of sensitivity to grass and wild grass pollens is expected to be higher than tree pollens due to a more limited exposure. Also, it has been long known that although the concentration of tree pollens in the atmosphere is higher, their allergenicity is lower than that of grass pollens (30,31).…”
Section: Discussionmentioning
confidence: 99%